Los cambios en la familia vistos desde la demografía; una breve reflexión - Quilodrán, Julieta (El Colegio de México A.C., 2008)
This text contains a series of reflections drawn from years of research and teaching on fertility and marriage rates, the latter being understood in its broadest sense of the family formation process. It begins by attempting to place the evolution of these two phenomena within the context of general demographic dynamics in order to highlight the principal changes observed in developed societies and the Latin American region. The demographic transition that took place over two centuries in Europe is occurring in less than one in the countries where it began in the 20th century. These phenomena -marriage rates and fertility- have been accompanied by two unexpected events: the decrease in fertility to below replacement levels and transformations in the formation and stability of conjugal couples. Within the familial sphere, the continuous decline in couples’ fertility has been accompanied by extra-marital sex, children born outside wedlock, birth control, the interruption of unions, remarriage and informal unions.The aim of the article is to analyze the aspects of marriage rates that are influencing the reproductive regime in the post-transitional era, which are precisely those that are at the center of the discussion on the second demographic transition.